Theoretical Evaluation and Comparative Study of Ultrasonic Velocities in Binary Liquid Mixtures of N-Methyl-2-pyrrolidone with Substituted Benzenes at Different Temperatures and Atmospheric Pressure - Bala Karuna Kumar, D.; Rayapa Reddy, K.; Srinivasa Rao, G.; Rama Rao, G.V.; Rambabu, C. (Asian Journal of Chemistry, 2012)
Theoretical velocities of binary liquid mixtures of N-methyl-2-pyrrolidone (NMP) with aniline (AB), bromobenzene (BB) and chlorobenzene (CB) at temperature = (303.15, 308.15, 313.15, 318.15) K and atmospheric pressure have been evaluated by using theoretical models such as Nomoto, Van Dael-Vangeel ideal mixing, impedance dependence, Rao's specific velocity method and Junjie's relations. Ultrasonic velocities and densities of these mixtures have also been measured experimentally as a function of composition of N-methyl-2-pyrrolidone and temperature. A good agreement is found between experimental and theoretical values. U2exp/U2imx has also been evaluated for non-ideality in the mixtures. Chi-square test for the goodness of the fit is applied to investigate the relative applicability of these theories to the present systems. The results are discussed in terms of intermolecular interactions between the component molecules in these binary liquid mixtures.